Toward Exploiting the Behavior of Niobium-Containing Mesoporous Silicates vs. Polyoxometalates in Catalysis - Wawrzynczak, Agata; Nowak, Izabela; Feliczak-Guzik, Agnieszka (Frontiers in Chemistry, 2018)
Classification of polyoxometalates (POMs) is based on their chemical composition, basically represented by two general formulae: a) [MmOy]p− b) [XxMmOy]q−, where M is the main transition metal, O is the oxygen atom and X can be a non-metal atom such as Si. Additionally, in the most cases, the structure of the polyoxometalates is derived from a combination of octahedral units MO6 with a central metal atom M and the oxygen atoms placed at their corners. In such octahedra, oxygen atoms allow the condensation between two octahedral units, while one oxygen atom (or max. two atoms) makes double bond with the central metal atom and is not shared with other metal atoms within the complex (terminal oxygens). On the other hand, niobium-containing mesoporous silicates contain mainly MO4 tetrahedra and reveal superior activity in heterogeneous catalysis. Thus the proper coordination of niobium is crucial for the catalytic activity and will be deeply discussed. The similarity in the catalytic behavior of niobium-polyoxometalates and heterogeneous niobium single-site catalysts in selective oxidations will be demonstrated.